The role of "fear of corticosteroids" in nonparticipation in early intervention with inhaled corticosteroids in asthma and COPD in general practice - van Grunsven, PM; van Schayck, CP; van Kollenburg, HJ; van Bosheide, K; van den Hoogen, HJ; Molema, J; van Weel, C (The European respiratory journal, 1998)
Treatment of chronic airflow obstruction with inhaled corticosteroids at an early stage has been shown to preserve the lung function. We tested the hypothesis that "fear of corticosteroids" may be an important reason for nonparticipation in the Detection, early Intervention and Monitoring programme on Chronic obstruction pulmonary disease (COPD) and Asthma ("DIMCA") project. One thousand seven hundred and forty nine adult subjects from 10 general practices were invited to participate in the several parts of the "DIMCA" programme. Refusers were questioned about the reason(s) for nonparticipation. Together the screening, monitoring and three drug interventions of the study showed on average 25-35% refusers. The most frequent reasons for nonparticipation were absence of pulmonary symptoms and lack of time. For those invited to take part in one of the three drug interventions, "dislike of medication" was the most important reason for nonparticipation (33, 45 and 67% of the refusers). "Fear of corticosteroids" specifically was the reason for nonparticipation in 8% of the refusers on the basis of "dislike of medication". We concluded that a specific fear of corticosteroids was not a major obstacle for early intervention with inhaled corticosteroids.